2003
DOI: 10.1038/sj.bjc.6601013
|View full text |Cite
|
Sign up to set email alerts
|

Biological response to hormonal manipulation in oestrogen receptor positive ductal carcinoma in situ of the breast

Abstract: Adjuvant antioestrogen therapy with tamoxifen is recommended for all women following breast-conserving surgery for ductal carcinoma in situ (DCIS) to reduce local recurrence, despite 50% of lesions being oestrogen receptor (OR) negative. We have investigated the response to hormone manipulation in DCIS by studying changes in epithelial proliferation and progesterone receptor (PR) expression as surrogate molecular markers of treatment effects in DCIS of known OR status. Women were identified who had undergone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…Gain of 17q has been associated with amplification of ERBB2, located at 17q12 (38). Studies have shown that the erbB2/her2/neu protein product is overexpressed in 60 -70% of DCIS by immunohistochemistry (39,40), although in only 20 -30% of invasive breast cancers. The higher prevalence of 17q gain in DCIS versus invasive ductal cancer is somewhat counterintuitive given the precursor-product relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…Gain of 17q has been associated with amplification of ERBB2, located at 17q12 (38). Studies have shown that the erbB2/her2/neu protein product is overexpressed in 60 -70% of DCIS by immunohistochemistry (39,40), although in only 20 -30% of invasive breast cancers. The higher prevalence of 17q gain in DCIS versus invasive ductal cancer is somewhat counterintuitive given the precursor-product relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 and ER scores were calculated as the percentage of positively stained nuclei. Oestrogen receptor positivity was defined as X5% stained nuclei, and has been used in previous studies in DCIS in our unit (Holland et al, 1997;Gandhi et al, 1998Gandhi et al, , 2000Boland et al, 2003b). For each section, a minimum of 1000 cells were scored across randomly selected areas of DCIS at a magnification of  400 using a grid graticule and cell counter.…”
Section: Evaluation Of Immunostainingmentioning
confidence: 99%
“…However, conservation surgery is associated with local recurrence rates of between 7% and 30% after 10 years of follow-up compared with <1% following mastectomy (3). Approximately half of all recurrences are invasive cancers (1,2).…”
mentioning
confidence: 99%
“…Most patients with DCIS are treated with breast conservation surgery with subsequent adjuvant therapy with radiation and/or tamoxifen (1,2). However, conservation surgery is associated with local recurrence rates of between 7% and 30% after 10 years of follow-up compared with <1% following mastectomy (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation